Die wichtigsten Schriftformen der Alten Welt - Thorn, Karl (ERDKUNDE, 1963)
It is well known that it is far from easy to delimit boundaries of cultural regions. There are, or were, however, certain interrelationships between the distribution of certain types of script on the one hand and certain physical-geo graphical or political conditions or processes on the other hand. Events of religious history or the causal connexion of types of script with types of language also point to definite areas. Thus together with a type of script come a whole host of cultural factors and with them areas of common social characteristics for the formation of which they are partly or solely responsible. It is surprising that seemingly neither Banse (organische Erdteile) nur Schmitthenner (Lebensräume) have recognised the important role which type of script can play in delimiting major cultural regions. The attempt undertaken in this paper to show the reasons for the distribution of the various types of script conveys information about the historical development of areas of writing. Since these are almost invariably also areas of a certain indigenous civilisation knowledge about areas of script contributes to a better appreciation of regions for whose character the human mind is responsible. These regions are partly coincident with physical-geographical units, partly there is an overlap and it is these latter cases which are particularly interesting.